PSYCHOLOGICAL FACTORS IN THE DEVELOPMENT OF STRESS RESILIENCE OF IT COMPANY EMPLOYEES: A THEORETICAL JUSTIFICATION - Dovbnia , Serhii (PSYCHOLOGICAL JOURNAL, 2025)
The article provides a generalized review of theoretical approaches to the concepts of stress and resilience, which are considered as a complex systemic characteristic of personality manifested through the integration of various levels of human life activity and professional functioning. These levels—stress and resilience—enable individuals to cope with difficult life situations without negative consequences for personal functioning and the social environment. The combination of these two concepts—stress and resilience—has led to the formation of the phenomenon of stress resilience, which is interpreted in psychological research as: an integral personality trait; a complex personal quality; the ability to withstand the negative impact of stress factors; and a complex systemic characteristic of the individual. Within the current spectrum of contemporary psychological research, particular attention is paid to the study of psychological characteristics of professional activity among IT company employees, whose work is accompanied by a significant number of stressors that are specific in nature. Based on the analysis of scientific studies, the following key stress factors were identified: informational uncertainty, increased responsibility, time pressure, interpersonal conflicts, and intrapersonal (role-related) conflicts. All of these stressors affect the personality and individual psychological characteristics of IT company employees, leading to an increase in negative emotional experiences and stress reactions, which in turn results in the emergence and accumulation of prolonged stress states. Prolonged exposure to stress significantly reduces the effectiveness and quality of professional performance of IT company employees and requires the mobilization of additional internal resources to maintain an optimal level of mental functioning. This is associated with a decrease in emotional satisfaction with the work process and its outcomes, as well as with the deformation of individual psychological traits and personality characteristics. The system of stress factors is extensive and diverse, as they are determined by the entire external organizational environment of professional activity, any component of which under certain conditions may become a source of stress. Therefore, stress resilience plays a crucial role in maintaining employees’ mental health and achieving high levels of professional performance under increasing stress loads. An important characteristic of stress resilience is the ability not only to maintain but also to enhance performance effectiveness in situations of intensified stress conditions. Stress resilience, the ability to establish constructive communication with different people, well-developed communication skills, and empathy are key qualities required of IT company employees. A high level of stress resilience enables IT professionals to cope with work-related tasks effectively and to provide meaningful support to clients in solving issues that are relevant to them. Thus, ensuring an optimal level of stress resilience among IT company employees is a highly relevant issue, as it contributes to maintaining psychophysiological well-being, behavioral adequacy, and productive professional activity in an extreme professional environment.